2018
DOI: 10.1021/acs.nanolett.8b02770
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Conserving Resonant Tunneling in Twist-Controlled WSe2-hBN-WSe2 Heterostructures

Abstract: We investigate interlayer tunneling in heterostructures consisting of two tungsten diselenide (WSe) monolayers with controlled rotational alignment, and separated by hexagonal boron nitride. In samples where the two WSe monolayers are rotationally aligned we observe resonant tunneling, manifested by a large conductance and negative differential resistance in the vicinity of zero interlayer bias, which stem from energy- and momentum-conserving tunneling. Because the spin-orbit coupling leads to coupled spin-val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Tunneling spectroscopy in van der Waals and other heterostructures is a powerful tool that can reveal unique information about the density of states (DOS) of the electrodes [1,2], about phonons (or other excitations) [3][4][5], about the chiral, valley [6] and spin states of the carriers [7,8] and their interactions [9]. Recently it was shown that the presence of defects in crystalline hexagonal boron nitride (h-BN) tunneling barriers can be detected in the tunneling spectra, which is dominated by Coulomb blockade effects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Tunneling spectroscopy in van der Waals and other heterostructures is a powerful tool that can reveal unique information about the density of states (DOS) of the electrodes [1,2], about phonons (or other excitations) [3][4][5], about the chiral, valley [6] and spin states of the carriers [7,8] and their interactions [9]. Recently it was shown that the presence of defects in crystalline hexagonal boron nitride (h-BN) tunneling barriers can be detected in the tunneling spectra, which is dominated by Coulomb blockade effects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous types of 2D materials have been implemented to fabricate high‐performance NDR devices. The critical performance metrics of PVR and NDR V at room temperature are compared with the state of the art of fabricated 2Ds‐based NDR devices including graphene [ 49,52,69–75 ] and other 2Ds [ 76–82 ] as well as commercialized RTDs [ 81,83,84 ] as illustrated in Figure 6 . Graphene‐channel‐based (graphene [Gr], [ 43,69 ] graphene nanoribbon [GNR], [ 67,71 ] fluorinated graphene [FGr], [ 40 ] graphene oxide [GO] [ 68 ] ) NDR devices were compared.…”
Section: Resultsmentioning
confidence: 99%
“…NDR near zero bias has been observed only in perfectly aligned WSe 2 /h‐BN/WSe 2 devices, supporting that NDR near zero bias is related to spin and valley properties of WSe 2. 66 Very recently, it was demonstrated in a TMDC/h‐BN/TMDC/Gr‐based RTT 67 that NDR occurs when the applied bias is close to the bandgap of the TMDC (Figure 3H). Therefore, resonant tunneling spectroscopy can be used to probe the bandgap of TMDCs without quasiparticle effects.…”
Section: H‐bn Tunneling Barriermentioning
confidence: 95%